Stability Analysis of Ecological Slopes Based on a 3D Finite Element Model - ZiFan Sui; Weijia Yuan; Wen Yi; Weihuan Yang (Advances in Materials Science and Engineering)
To explore the effect of grass and shrub plant roots on the stability of soil slopes in rainy areas in the south, this article relies on the Longlang Expressway construction project. Cynodon dactylon and Magnolia multiflora were selected as research subjects. The plant distribution characteristics and mechanical properties are analyzed. This paper uses ABAQUS finite element software to construct a 3D model of the planted slope in the test section. The stress and strain on the root system and the soil were observed, and the variation law of slope stability before and after plant protection under different rainfall events was compared and analyzed. The test and simulation results show that the root content of Cynodon dactylon gradually decreases with increasing depth. Cynodon dactylon was mainly distributed in the 0–30 cm soil body, and its effect on improving the cohesion of the soil body reached 75%. Magnolia multiflora belongs to vertical roots and has a strong and longer main root with relatively developed lateral roots. Its root system passes through the sliding surface of the slope bottom, which reduces the maximum equivalent plastic stress generated inside the slope by 61%. When the total rainfall duration is unchanged, under the three rainfall intensities of small, medium, and large, herbaceous plants increase the safety factor of the soil by 1.33%, 2.08%, and 6.1%, respectively, and the roots of shrubs increase the safety factor of the soil by 3.29%, 4.08%, and 4.32%, respectively. When the rainfall intensity does not change, as the rainfall time increases, the effect of plants on the slope safety factor first gradually increases and eventually stabilizes. The research results provide a reliable theoretical basis for analyzing the effect of plant roots on soil consolidation and slope protection, and they also lay a technical foundation for the promotion and application of ecological slope protection technology.